1997
DOI: 10.1136/bjo.81.10.840
|View full text |Cite
|
Sign up to set email alerts
|

Aging changes of the optic nerve head in relation to open angle glaucoma

Abstract: Aims-To determine the age related changes in optic nerve head structure in a group of normal subjects and assess the significance of any changes in relation to those found in open angle glaucoma. Methods-A group of 88 white volunteers and friends and spouses of patients with a normal visual field and normal intraocular pressure was studied. Two diVerent imaging and measurement devices were used (computer assisted planimetry and scanning laser ophthalmoscopy), and the results from each were compared. Measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 47 publications
6
49
1
3
Order By: Relevance
“…Several papers have reported no correlation between age and the optic disc (Britton et al 1987;Carpel & Engstrom 1981;Funk et al 1989;Gundersen et al 1998;Jonas et al 1988;Varma et al 1994). On the other hand, some papers have reported such a correlation (Garway-Heath et al 1997;Healey et al 1997;Tsai et al 1992).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several papers have reported no correlation between age and the optic disc (Britton et al 1987;Carpel & Engstrom 1981;Funk et al 1989;Gundersen et al 1998;Jonas et al 1988;Varma et al 1994). On the other hand, some papers have reported such a correlation (Garway-Heath et al 1997;Healey et al 1997;Tsai et al 1992).…”
Section: Discussionmentioning
confidence: 98%
“…(Balazsi et al 1984;Mikelberg et al 1991;Repka & Quigley 1989). Indeed, several reports have revealed age-related changes in the optic disc configuration (Carpel & Engstrom 1981;Garway-Heath et al 1997;Healey et al 1997;Tsai et al 1992), while other reports have demonstrated no age-related changes (Britton et al 1987;Funk et al 1989;Gundersen et al 1998;Jonas et al 1988;Varma et al 1994). There are few reports, however, regarding factors influencing the normal optic disc among Asian people.…”
mentioning
confidence: 99%
“…The correlation between age and HRT parameters remains controversial [20][21][22], with some researchers reporting age-related optic nerve head changes in cross-sectional and longitudinal studies [20,21] and others finding no correlation between age and HRT parameters in a cross-sectional study [22]. Second, only a small number of SSOH and NTG subjects were enrolled in our study.…”
Section: Discussionmentioning
confidence: 93%
“…[10][11][12] Also, although assessment of visual function is critically important for all patients with glaucoma, there is evidence to suggest that many patients may show evidence of progressive optic disc damage before functional loss is detected by SAP. Both the Ocular Hypertension Treatment Study 13 and the European Glaucoma Prevention Study 14 demonstrated that a substantial proportion of patients with ocular hypertension who developed glaucoma showed a change first in optic disc photographs. However, despite being included as end points for glaucoma conversion in these studies, progressive optic disc damage has not yet been demonstrated to translate into worse clinically relevant outcomes for these patients.…”
Section: Neuroretinal Rim Loss and Retinal Nerve Fiber Layer (Rnfl) Dmentioning
confidence: 99%
“…[10][11][12][13][14][15] Because PPA is present in 15%-20% of normal eyes, its presence is less specific for glaucoma than DH, which occurs only in 0.6% of healthy eyes. 14,16 Given that DH is transient, lasting weeks to months, and that PPA is stable and progressive, it maybe advantageous to rely on PPA parameters for glaucoma diagnosis and monitoring. 11,15 PPA and PPA have been evaluated in glaucoma using quantitative analysis of optic nerve photographs (morphometry) typically by manually outlining and measuring the area of PPA using a slide projector, imaging processing software, or with confocal scanning laser ophthalmoscopy.…”
Section: Wwwintechopencommentioning
confidence: 99%